IMPROVING STUDENTS’ WRITING ABILITY ON DESCRIPTIVE PARAGRAPH THROUGH COPYING A PARAGRAPH - . Mariam; Alber Rufinus; Urai Salam (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2016)
Abstract: Research was conducted in two cycles. In the first cycle activities,  the students are asked to copy a descriptive paragraph same with paragraph model correctly.The results of the students value obtained in these activities reached an average value of 80.00. While activity in the second cycle, students are asked to rewrite a descriptive paragraph by replacing the name and use the appropriate personal pronoun with suitable  name that is provided in parentheses. The result of the students’values  reached an average value of 84.00. Based on the results of these activities carried out on both cycle can be concluded that  the students’ ability improved  in copying a paragraph.  This means that the act of the copying strategy of hypothesis  use to improve students’ writing skills in the classroom prove. It has reached a value above the average KKM is 70.00. Thus the author concludes that copying a paragraph improve skills in writing.Thus, the authors suggest that teachers should determine a strategy is suitable or appropriate for students who are taught in accordance with the condition and may help them in writing. Keyword: Writing ability, copying descriptive paragraph Abstract: Penelitian ini dilakukan dalam dua siklus. Dalam kegiatan siklus pertama, siswa diminta untuk menyalin sebuah paragraf deskriptif yang sama dengan model kalimat dengan benar. Hasil nilai siswa yang diperoleh dalam kegiatan ini mencapai nilai rata-rata 80,00. Sementara aktivitas pada siklus kedua, siswa diminta untuk menulis ulang paragraf deskriptif dengan mengganti nama dan menggunakan kata ganti diri yang sesuai dengan nama yang cocok yang disediakan dalam kurung. Hasil students'values ​​mencapai nilai rata-rata 84,00. Berdasarkan hasil kegiatan ini dilakukan pada kedua siklus dapat disimpulkan bahwa kemampuan siswa meningkat dalam menyalin paragraf. Ini berarti bahwa tindakan strategi menyalin hipotesis digunakan untuk meningkatkan siswa keterampilan menulis di kelas membuktikan. Telah mencapai nilai di atas rata-rata KKM adalah 70,00. Dengan demikian penulis menyimpulkan bahwa menyalin paragraf meningkatkan keterampilan dalam menulis. Jadi, penulis menyarankan bahwa guru harus menentukan strategi cocok atau sesuai untuk siswa yang diajar sesuai dengan kondisi dan dapat membantu mereka dalam menulis. Kata Kunci : Kemampuan siswa menulis, menyalin ayat deskriptif